(untitled) (Research Papers, 2022)
The subject of research in this article is food waste, which represents a significant share of total biodegradable waste. It gives a modern view of the legislative framework built over the years, incl. >including existing national and European policies.The tools used are successful foreign examples from practice, which clearly outline the positive aspects of the actions for the overall management of biodegradable waste. The article presents an empirical part in the form of systematized data, the values ?? > of which direct the reader’s attention to the relevance of the topic. A major share of the total amount of biodegradable waste is the share of food waste, and households, in turn, are the largest generator of food waste. The need to take action towards sustainable recovery of biodegradable household waste is considered.The purpose of this article is, based on the review, to make a recommendation for improving the management of food waste in our country.